PERANAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH DISIPLIN KERJA KOMPETENSI DAN LINGKUNGAN KERJA TERHADAP PEGAWAI PT. SINERGI GULA NUSANTARA PG. WRINGIN ANOM KABUPATEN SITUBONDO - Dery Iman Santoso; Ida Subaida; Yudha Praja (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
This study aims to analyze the role of job satisfaction in mediating the influence of work discipline, competence, and work environment on employee performance at PT. Sinergi Gula Nusantara PG. Wringin Anom, Situbondo Regency. The problems identified in the company include low discipline, suboptimal employee competence, and a less supportive work environment, leading to decreased sugar production. This research applies a quantitative method with a descriptive approach. Data were collected through questionnaires from 52 employees and analyzed using Partial Least Square - Structural Equation Modeling (PLS-SEM). The results reveal that work discipline, competence, and work environment have a positive and significant influence on job satisfaction. Furthermore, these three variables significantly affect performance both directly and indirectly through job satisfaction as a mediating variable. Job satisfaction is proven to play a crucial role in improving employee performance. This study contributes to company management in formulating strategies to enhance employee performance through strengthened discipline, increased competence, and the creation of a conducive and supportive work environment.